Anaplastic meningioma in an adolescent: Case report and brief literature review - Ahmad Faried; Yosafat Kurniawan Sugiarto; Arwinder Singh Gill; Muhammad Firdaus; Oskar Ady Widarta; Farilaila Rayhani (Fakultas Kedokteran Universitas Tarumanagara, 2023)
Anaplastic meningioma is an uncommon neoplasm in childhood and adolescence. In contrast to the case in adults, pediatrics have a predominance of males over females. We report a case of a 17 years old with progressive scalp swelling on the right side. Patient underwent subtotal tumor resection at previous hospital three months ago. The operation was stopped due to extensive bleeding. Radiological investigations revealed a dura-based tumor with a cystic component. Following preoperative embolization, a craniotomy was done, and the tumor was almost completely removed. The tumor's histopathological analysis revealed characteristics of an anaplastic meningioma. The aggressive behavior of this tumor necessitates meticulous monitoring of therapeutic measures in such patients.